Current Challenges of Personal Branding - Nagy, Adrián; Molnár, Dániel; Szikszai-Németh, Ketrin (International Journal of Engineering and Management Sciences, 2018)
The purpose of this study is to highlight the importance of collaborating with influencers as one of the most recent marketing tools. This article is intended to help brands and influenceres in critical situations, such as problems encountered in measuring performance or finding the right strategic partners, as mentioned in the literature. In the future – among the many potential research areas – we plan to study the self-branding of athletes and find key factors that distinguish influencers from other people.